American slavery and labour market power. Issue 1 (2nd January 2020) - Naidu, Suresh
ABSTRACT: In this article I discuss the micro-economics of American slavery in light of recent research on monopsonistic labour markets. I argue that the defining characteristic of coerced labour, the threat of violence to prevent voluntary quits from a job, can be helpfully understood by contrasting it with free labour markets that are riven with imperfect competition and agency problems. American slavery looks closer to the textbook competitive model of labour markets than does free labour.